Artificial intelligence (AI) in efforts to prevent teenage suicide: literature review - Rosadi, Muhammad Imron; Yovalwan, Tahratul; Asaduddin, Akmal Zaki (Media Keperawatan Indonesia, 2024)
Suicide is a highly complex mental health issue that is a leading cause of death and requires efforts to reduce the number of victims. In the modern technology era, the utilization of artificial intelligence (AI) is seen as a suicide prevention initiative and presents a significant challenge in global prevention efforts. This literature review aims to determine the use of Artificial Intelligence (AI) in efforts to prevent teenage suicide. The research method utilizes the PRISMA guidelines. This literature review employs a systematic approach and selection process. Literature sources were searched from Proquest, PubMed, Google Scholar, and Scopus databases. Out of the 7 reviewed articles, 2 were from South Korea, 2 from the United States, and the remaining 3 were from Spain, Italy, and Canada. The Cohort research design was the most prevalent in this literature review (N = 5), and one study used an RCT design (N = 1), while a Cross-Sectional research design was employed in one study (N = 1). Overall, it indicates that AI is capable of predicting suicide risk and preventing suicide. The results of the literature review indicate that the use of AI technology has benefits in preventing teenage suicide.